BATU BARA SEBAGAI ADSORBEN - Adeko, Riang (JURNAL MEDIA KESEHATAN, 2017)
Providing clean water to the community has a very important role inimproving the environment or public health, which has a role in reducing the number ofpeople with the disease, especially those related to water, and its role in improving thestandard or level / quality of life. initial survey conducted on February 20, 2016 in RW.03 Village Rawa Makmur Permai Bengkulu City after measurements were obtained Iron(Fe) 0.9 mg / L; Manganese (Mn) of 0.87 mg / L. From the measurement results in theinitial survey is known that water wells RW.03 village residents Rawa Makmur PermaiBengkulu city still exceeds the threshold required by Permenkes RI 416 / Menkes / per /IX / 1990. The purpose of this study was to determine the reduced levels of Fe and Mnbefore and after treatment by using a variation of coal thickness of 20 cm, 30 cm and 50cm as well as to the most effective menegetahui thickness variation to reduce levels of Feand Mn. This research uses experimental methods pure (True Experimental) experimentaldesign with Pre-Post test, the research conducted before and after treatment. Then lookfor the difference between the measurement of both, and the difference is considered as aresult of treatment. Results of the study is the reduction of Fe content using coaldecreased by 42% and decreased levels of Mn using coal decreased by 35%. The resultshowed that the thicker the more effective adsorbent decline.